Uji Efektivitas Getah Pelepah Pohon Pisang Mahuli Dengan Metode Difusi Cakram Sebagai Antibakteri Staphylococcus aureus - Halimah, Nur; Salman, Yuliana; Risnawati, Risnawati; Hidriya, Hajrah (Politeknik Unggulan Kalimantan, 2024)
A wound can be interpreted as a break or loss of continuity of skin tissue, with disruption to the anatomical structure and physiology of human body organs such as skin, hypodermis, muscles, tendons, nerves, blood vessels and even bones. Wounds that are not handled properly can easily become infected which can be caused by Staphylococcus aureus. This study aims to determine the effectiveness of Mahuli banana tree midrib sap using the disc diffusion method The research design used was an experimental study with a Completely Randomized Design (CRD) with a test only control group design pattern. The research samples consisted of Mahuli banana tree midrib sap and a culture of Staphylococcus aureus bacteria. The antibacterial test method uses the disc diffusion method by measuring the diameter of the clear zone in the media. The data collected was analyzed statistically using(ANOVA and continued with the Post Hoc test. Mahuli banana tree midrib sap is effective in inhibiting the growth of Staphylococcus aureus bacteria at the concentration 60% with a significance value of 0.078 (α>0.05). Mahuli bananas midrib sap contain alkaloids, saponins, tannins and flavonoids which act as antibacterials.